Pilates for living : get stronger, fitter and healthier for an active later life - Angell, Harri (Bloomsbury Sport, 2018)
"Pilates for living contains over 70 simple and effective exercises, suitable for all levels and abilities, with clear explanations, tips and modification suggestions. You will also find expert osteopathic advice and motivational interviews"--Back cover.